2010
DOI: 10.1136/jramc-156-03-06
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Airway Management – a Medical Emergency Response Team Perspective

Abstract: The figure of 56 patients requiring advanced airway management is at the higher end of the range expected from the study of historical military data. This may reflect the doctrine of "intelligent tasking", that is sending this physician-led team to the most seriously injured casualties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Use of a multidisciplinary team approach to the management of several acute situations, such as myocardial infarction, coronary dissection, major trauma, and cardiopulmonary arrest, has been found to significantly influence patient outcomes . Similarly, a well‐equipped, multidisciplinary team approach to managing difficult airway situations could improve the efficiency of care and teamwork, in addition to reducing mortality and complications . Our institution introduced a DART that uses an approach similar to that used in the operating room for intubation of patients with difficult airways .…”
Section: Discussionmentioning
confidence: 99%
“…Use of a multidisciplinary team approach to the management of several acute situations, such as myocardial infarction, coronary dissection, major trauma, and cardiopulmonary arrest, has been found to significantly influence patient outcomes . Similarly, a well‐equipped, multidisciplinary team approach to managing difficult airway situations could improve the efficiency of care and teamwork, in addition to reducing mortality and complications . Our institution introduced a DART that uses an approach similar to that used in the operating room for intubation of patients with difficult airways .…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies advocated the MET intervention for airway management. One study showed that pediatric MET was associated with a significant decrease in the incidence of respiratory arrest in a general ward,12 and another study showed that intervention by the Medical Emergency Response Team, a part of the British Military's trauma system, and advanced airway management including RSI increased survival in the peri-evacuation phase 13. Moreover, our present study demonstrated an association with MET intervention and improvements of various physiologic parameters in critically ill adult patients during airway management.…”
Section: Discussionmentioning
confidence: 99%
“…There is an introduction to PHEM outlining how patients would be transported to the contingency facility and the treatment that they could potentially receive 22 23. There is also a discussion on the role of the Critical Care Air Support Team (CCAST) with an overview of their capabilities and preparing to package a patient for a CCAST transfer 24…”
Section: Core Coursesmentioning
confidence: 99%